KONFLIK SUMBER DAYA ARKEOLOGI PADA ERA OTONOMI DAERAH - Bambang Sulistyanto (Balai Arkeologi Kalimantan Selatan, 2009)
The benefiting from archaeological resource during the district autonomy era -prior to the reformation era- in Indonesia shows varieties of conflict concerning either the factors which have caused the problems or the actors involved in the conflict. My research suggests that conflict of benefiting from archaeological resources had appeared due to mishmash of several old issue which was developed into new issue as a result of the reformation movement. Old issues which had to be dealt with were the theft, condemnation and destruction of cultural heritage. Such issue occured becauce of clashes of interest between the government’s intention to preserve archaeological resources and the basic economic needs of the community surround the site to provide a secure life. Meanwhile, new issues surfaced due to the development of democracy euphoria within the district goverment as the consequence of the commencement of Law number 32 tahun year 2004 concerning District Autonomy. Horizontal conflict between the central goverment in Jakarta and district goverments has emerged in regard to differences of perception on how to give meaning to archaeological resources, which eventually caused differences of interest in benefiting from archaeological resources. Nevertheless, since the commencement of the reformation era in Indonesia, the people have been expreriencing enlightenment beyond expetation. Therefore, it is not surprising that the people of Indonesia show admirable response to deal with problem solving in manging the archaeological resources; they are more proactive and even demand their rights to be involved in managing the archaeological resources, which are essentially belong to the people of Indonesia. This article discusses the conflict resolution in a cultural management resourch approach.